Investigation of iron selectivity behavior of copper smelter slag flotation tailing with hematitization baking and base metals leaching methods - UZUN KART, ELİF (OFICYNA WYDAWNICZA POLITECHNIKI WROCLAWSKIEJ, 2021)
In this study, iron selectivity behaviour of copper smelter slag (CSS) flotation tailings (38.08% Fe, 0.35% Cu, 4.48% Zn, 0.16% Co, 0.37% S) having fayalite and magnetite as major minerals was investigated with hematitization baking and base metals leaching methods using mineralogical and chemical analyses. For selectivity of iron, it was baked at temperatures of 650-690-700-710-730 degrees C. The aim of the baking is to transform the almost all of the iron in the fayalite into the oxidized (non-soluble) form and the base metals into the sulphated (soluble) form. The temperature that had the lowest hematitization rate of iron was found to be 650 degrees C, and the highest temperature was found to be 730 degrees C. To examine the dissolution behaviour of baked CSS flotation tailing was leached at 50 degrees C at a 1/10 (w/v) for 1 hour by using water. After baking at 690 degrees C calcine and leaching residue, S values were determinated to be approximately 17% and 9%, respectively. Baking made at 700 degrees C, amount of sulfate also decreased to 10% and S content was measured as 4% of its leaching residue. As a result of this study, 690 degrees C/700 degrees C was determined as optimum conditions of hematitization baking and base metals were extracted selectively when the iron was remained at leaching residue in Fe2O3 phase. It was determined that, hematitization is high and the sulphates of the base metals are preserved at 700 degrees C temperature. The fayalite phase completely decomposed into Si-O/Fe-O/Zn-S-O/Co-S-O compounds at 700 degrees C baking which was the highest iron selective and base metals dissolute temperature.
Keywords: iron selectivity; hematitization baking; copper smelter slag flotation tailing; base metal leaching; CONVERTER SLAG; SULFURIC-ACID; AMMONIUM-SULFATE; RECOVERY; NICKEL; COBALT; EXTRACTION; VALUES; ZINC